Gender and the local-global nexus theory, research, and action - Demos, Vasilikie P.; Segal, Marcia Texler, 1940- (Advances in gender research, 2006)
The nine papers in this volume have a world in which the local/global connection is salient as background. Examining gender and its implications for feminist action within this setting, they fall into three overlapping categories. The first, theory, involves the theoretical consideration of gender across place and time. The second, research, reveals cultural differences in attitudes toward gender, and the third, action, concerns the feminist implications of gender as hierarchy. Disciplines represented include archaeology, cultural anthropology, sociology, and urban studies. Comparing, contrasting, and critiquing, authors based in Australia, Brazil, Italy, New Zealand, and the United States report research findings and personal experiences from their home countries as well as Canada, Mexico, Siberia, Slovakia, and a range of Asian nations. In every instance, gender dynamics are shown to be challenging and complex and new insights and directions for gender research, theory and action are revealed. It discusses theory, research and action tied to gender and geographic location. A variety of cultures are represented from diverse countries in the Americas, Asia and Europe. It provides new insights and directions for gender research.